(untitled) (Academicia Globe: Inderscience Research, 2023)
This paper presents an analysis of the acoustic characteristics of exhaust gas cleaning devices used in the exhaust systems of automobile engines, which should be taken into account in order to comply with the current standards for harmful substances emitted from automobile engines.